A terceirização em um campus do Instituto Federal do Maranhão: um estudo sobre saúde e subjetividade das agentes de limpeza - MATOS, Thamires Thayanne Cerqueira (2021)
The idea of work has undergone significant changes over time, however, it is certain that through it man differs from other forms of life, so work is a fundamental condition for the exercise of the social role. However, work is seen as a commodity, within a capitalist logic, so work also brings the presence of suffering, causing pleasure and displeasure. The new labor legislation contributes to this perspective since they increase company guarantees by reducing institutional protection to workers, thus reducing the rights once conquered by workers, also accentuating gender inequality, going against the feminist struggles of the last century. Based on this understanding, the main objective of this work is to analyze the impacts of new labor legislation from the point of view of health and subjectivity of outsourced workers in the cleaning sector of the Federal Institute of Maranhão (IFMA) Campus Monte Castelo, identifying points in these legislations that have direct repercussions for working women. The research was qualitative in nature and the theoretical-methodological framework that guided it was the Psychodynamics of Work, in conjunction with the Sociology of Work and the Dialectical-Historical Materialism. Six female cleaning agents participated in this study. The main results of the study point to work that is very similar to domestic work, with little visibility, precariousness, with low salaries and undervalued by society.